2008
DOI: 10.1007/s10765-008-0385-1
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Budgets for Calibration of Radiation Thermometers below the Silver Point

Abstract: Below the freezing point of silver, radiation thermometers are generally calibrated by implementing the multi-point interpolation method using blackbody measurements at three or more calibration points, rather than the ITS-90 extrapolation technique. The interpolation method eliminates the need to measure the spectral responsivity and provides greater accuracy at the longer wavelengths required below the silver point. This article identifies all the sources of uncertainty associated with the interpolation meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 24 publications
(26 reference statements)
1
68
0
3
Order By: Relevance
“…For temperatures below 1000ºC the signal of an RT is well described by the Sakuma-Hattori equation [7]:…”
Section: Temperature Deviations Due To Sse For Direct Temperature Reamentioning
confidence: 99%
See 1 more Smart Citation
“…For temperatures below 1000ºC the signal of an RT is well described by the Sakuma-Hattori equation [7]:…”
Section: Temperature Deviations Due To Sse For Direct Temperature Reamentioning
confidence: 99%
“…Sometimes it is more useful to calculate the temperature variation as a function of the measured signal variation, following a procedure similar to that in [7]. In general, this relation is given by:…”
Section: Temperature Deviations Due To Sse For Direct Temperature Reamentioning
confidence: 99%
“…The method described in [17,18] was used to derive two different uncertainty budgets for T Au depending on whether the extrapolation or interpolation approach has been used. Uncertainty components used in [11] for the determination of the budget for T Cu also apply for the present exercise.…”
Section: Uncertaintiesmentioning
confidence: 99%
“…It is difficult to measure the non-linearity effect in the infrared region; therefore, the effect is evaluated as follows. Regarding the nonlinearity of the InSb detector, it is reported that the detector should be linear in the modest range of L(800 • C)/L(157 • C) = 176, while for the wider range of L(960 • C)/L(20 • C) = 15500, a nonlinearity of 1 × 10 −3 (normal thermometer) or 1 × 10 −4 (best thermometer) is expected [16,18]. Here, L is the Planck radiance.…”
Section: Detector Noise and Non-linearitymentioning
confidence: 99%